2016
DOI: 10.1093/neuonc/now198
|View full text |Cite
|
Sign up to set email alerts
|

Immune modulatory nanoparticle therapeutics for intracerebral glioma

Abstract: 372Most preclinical therapeutic studies of microRNAs (miRs) and small interfering (si)RNAs have provided "proof of principle" that upon ex vivo transfection of cancer cells, a therapeutic effect can be obtained. [1][2][3] We previously demonstrated that the need to transfect could potentially be overcome by using miR to directly modulate the immune system and initiate antitumor cytotoxicity. 4 Malignant cells express various antigens recognized by the immune system, but antitumor cytotoxicity is restrained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…There is an expanding library of targeted agents being developed for and tested in canine brain tumors, and these agents represent a wide variety of mechanistic approaches including protease-conjugated oncolytic viruses, immunomodulatory microRNAs or small interfering RNAs, immune-checkpoint inhibitors, apoptosis promoters, radiosensitizing agents, and nanoparticular cytotoxic drugs. These compounds have shown promising anti-tumor effects in vitro or in vivo against non-CNS tumors, the ability to penetrate the BBB when administered systemically, or favorable safety and pharmacokinetic profiles in healthy dogs, and are currently in early phase trials in dogs with tumors (197, 203–206). Proof-of principle studies have demonstrated that both EGFR targeted, doxorubicin loaded minicells (204) and PAC-1, a pro-apoptotic, BBB-penetrant small molecule activator of procaspase-3 are capable of achieving clinically relevant intratumoral concentrations when administered systemically to dogs with naturally brain tumors (205).…”
Section: Novel Therapeutic Approachesmentioning
confidence: 99%
“…There is an expanding library of targeted agents being developed for and tested in canine brain tumors, and these agents represent a wide variety of mechanistic approaches including protease-conjugated oncolytic viruses, immunomodulatory microRNAs or small interfering RNAs, immune-checkpoint inhibitors, apoptosis promoters, radiosensitizing agents, and nanoparticular cytotoxic drugs. These compounds have shown promising anti-tumor effects in vitro or in vivo against non-CNS tumors, the ability to penetrate the BBB when administered systemically, or favorable safety and pharmacokinetic profiles in healthy dogs, and are currently in early phase trials in dogs with tumors (197, 203–206). Proof-of principle studies have demonstrated that both EGFR targeted, doxorubicin loaded minicells (204) and PAC-1, a pro-apoptotic, BBB-penetrant small molecule activator of procaspase-3 are capable of achieving clinically relevant intratumoral concentrations when administered systemically to dogs with naturally brain tumors (205).…”
Section: Novel Therapeutic Approachesmentioning
confidence: 99%
“…LNP formulation of the ANDV DNA vaccine results in a rapid, dose dependent neutralizing antibody response in vaccinated rabbits. Application of Arcturus's LUNAR ® technology results in increased delivery of mRNA into the cell and a concomitant increase in production of the encoded protein in vitro an in vivo 18,19 . We hypothesized that formulation of DNA with the same LNP would have a similar effect.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we demonstrate that combining DSJI with a DNA vaccine formulated with a lipid nanoparticle (LNP) carrier, which was originally developed for RNA, can further increase DNA vaccine immunogenicity in non-rodent laboratory animals including rabbits and nonhuman primates (NHPs). The LNP carrier is part of a technology known as LUNAR ® (Lipid-enabled nucleic acid delivery reagent) and has been shown to be effective and safe for up to 10 mg/kg of RNA in mice 18,19 . Having found that LNP formulation of DNA could increase immunogenicity, probably by increasing DNA uptake and subsequent immunogen production, we applied the technology to a product-oriented application: improving production of fully human polyclonal antibodies in transchromosomic (Tc) bovines-animals engineered to produce human immunoglobulins (Ig).…”
mentioning
confidence: 99%
“…Therefore, both local and systemic administration of miR-124 mimics seem a promising therapeutic for glioma treatments. The efficacy of systemically injected miR-124 encapsulated in bilipid nanoparticles or overexpressed in exosomes has been tested in murine models of GBM and suggested survival benefit [ 293 , 294 ]. In addition, miR-124 delivery to orthotopic U87 tumors was attempted by intratumor injections of the miR-124-overexpressing mesenchymal stem cells [ 295 , 296 ].…”
Section: Microrna Normalization By Otmentioning
confidence: 99%